2019
DOI: 10.1097/jpa.0000000000000266
|View full text |Cite
|
Sign up to set email alerts
|

Student-Led Mobile Health Clinic: Patients Served and Learning Experience

Abstract: Purpose Community medicine curriculum prepares physician assistant (PA) students to provide services to vulnerable and underserved populations. This article describes a service-learning model that uses a mobile health clinic (MHC) experience as part of the community medicine rotation. It provides an overview of the clinic's operation, patient documentation and characteristics, and student learning experiences. Methods Students collected demographic info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…A total of 10 articles were included in this scoping review after meeting the study inclusion criteria. 2,[8][9][10][11][12][13][14][15][16] Table 2 shows the characteristics of each study's SL project, including how many disciplines were involved in the project, the number of students, type of reflection, name of community partner, whether the objectives of the course were aligned with the SL activity, whether there was reciprocity between the students and the community partner interests, the length of the SL hands-on activity, the name of the course and if the course was taken for credit, the data evaluation method, and the outcome of the service-learning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 10 articles were included in this scoping review after meeting the study inclusion criteria. 2,[8][9][10][11][12][13][14][15][16] Table 2 shows the characteristics of each study's SL project, including how many disciplines were involved in the project, the number of students, type of reflection, name of community partner, whether the objectives of the course were aligned with the SL activity, whether there was reciprocity between the students and the community partner interests, the length of the SL hands-on activity, the name of the course and if the course was taken for credit, the data evaluation method, and the outcome of the service-learning.…”
Section: Resultsmentioning
confidence: 99%
“…2,16 Data on reflections were collected either in a written format, 10,11,[13][14][15][16] orally, 12 or using both oral and written formats. 2,8,9 All studies reported improvements in student learning related to their objectives. However, information on how they assessed their results (their evaluation method) to show improvement was not available for 3 of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…1 , 39 , 45 , 74 , 103 Of the articles reviewed, 76.1% (n = 169) explicitly identified use of a static site where the initiative was situated in a physical location (eg, church, shelter, etc. ), 6.3% were mobile to serve clients in various places, 18 , 22 , 35 , 39 , 41 , 52 , 53 , 57 , 70 , 75 , 88 , 107 and other sites, such as immunization clinics, were identified as temporary. 54 , 56 , 76 Static locations were frequently associated with churches and religious organizations (eg, Salvation Army and North Dallas Shared Ministries) 29 , 39 , 43 , 45 , 52 , 53 , 61 , 65 , 70 , 71 but also with non-profit and non-government organizations, such as shelters, recovery centers, and other associations.…”
Section: Antecedents For Student-run Initiativesmentioning
confidence: 99%
“…2,22,91,104 In many articles it was evident that some educational institutions or specific departments played a very active part in running and managing the student-run initiatives in conjunction with offering courses, creating clinical experiences or providing clinical placements. 1,34,41,44,56,57,75,95,[105][106][107] While educational preparation of students was noted as a motivation for this level of engagement by institutions, such as providing interprofessional education, practical experience, or exposure to specific populations, 6,29,35,43,85,89,102,107,108 community engagement, mandatory service learning, and provision of service to stakeholders, including the public, were also reported. 18,21,35,54,70,73,98 Active recruitment of students to programs or provision of innovative services, for example collaborative programs, were other motivations cited for educational institutions to formally be involved with student-run initiatives.…”
Section: Affiliation With Academic Unitmentioning
confidence: 99%
“…Dermatologic conditions were one of the major physical health concerns among PEH. 10,13,15,49,54,57,80 According to all extracted studies, the prevalence of skin conditions ranged from 16.6% to 53.5%. 10,11,15,25,57,64,80 Several studies described statistically significant higher prevalence of dermatologic conditions among PEH compared to the general population.…”
Section: Dermatologic Conditions In Adult Populationmentioning
confidence: 99%